Perancangan Tabung Reaktor pada Kompor Berbahan Bakar Kaleng Bekas - Sukadi; Hilda Porawati (Jurnal INOVATOR, 2019)
One example of the type of metal waste that can be managed is Aluminum such as used soft drink cans. One of the technological ways that can be developed to process the used soft drink cans is by recycling. The recycling process that can be done is to use a hydrolysis process that is mixing water, NaOH and scrap cans. The hydrolysis process requires the main components in the form of a hydrolysis reactor. In this research a hydrolysis reactor has been designed for the production of hydrogen gas with an operational pressure design of 300 psi, the dimensions of the reactor are 300 mm x 600 mm high. Wall thickness of 1.21 mm. and reactor material from JIS G 3116 plate.